Interaction of Pseudomonas aeruginosa biofilm with inflammatory cytokines and immune cells - Rahman, Tamanna (2016)
Colonisation and persistent lung infection by pathogens, mainly Pseudomonas aeruginosa (PA), is an important cause of morbidity and mortality in Cystic Fibrosis patients. PA persists inside the lungs by forming drug-resistant biofilms. Investigation into the behaviour of bacterial cells within these structures and their response to components of the innate immune response will give us an insight into novel approaches to combat infection. The main aim of this thesis was investigate the effect of inflammatory mediators such as cytokines and immune cells on the development of PA biofilms. For this the BioFlux system and PA expressing green fluorescent protein were used to generate biofilms. After incubation with serum, cytokines such as GM-CSF and IFN-γ, changes in the characteristic of the biofilms were analysed. No significant changes on PA biofilms were observed in the presence of the cytokines but human serum was shown to have an inhibitory effect. Incubation of PA biofilms with labelled purified human monocytes and macrophages indicate that macrophages, unlike monocytes attached to PA biofilms. Cell surface receptors expressed by monocytes and macrophages were compared and, as previously described, high mannose receptor (MR) expression was found in macrophages. MR is a carbohydrate binding receptor that plays a crucial role in innate immunity. MR binds mannose-rich carbohydrates through C-type lectin-like domains (CTLD) 4 to 7. Using a recombinant protein containing the mannose binding region of MR (CTLD 4-7-Fc) it was found that MR can directly interact with PA biofilms and that this binding is increased when Psl expression is increased. Furthermore CTLD 4-7-Fc was shown to bind crude extracts of carbohydrates from PA biofilm enriched for the extracellular polysaccharide Psl. We hypothesize that MR expressed by macrophages and dendritic cells might contribute to PA recognition through Psl. Future work will explore the capability of immune mammalian C-type lectins to recognise PA biofilms and purified Psl and elucidate the role of Psl in modulating the recognition of PA by immune cells using PA strains expressing different combinations of extracellular polysaccharides. Our results will shed light on the impact of Psl on the immune recognition of PA, and might open the avenues for the discovery of novel therapeutic targets. Dispersion is the final stage of the biofilm cycle and contributes to dispersal and transmission of pathogens to colonize new sites. Till now not many studies have focused on the role of dispersion in pathogenesis. Thus the present study also focused on the contribution of a dispersal molecule produced during PA biofilm formation termed cis-2-decenoic acid (CDA) and analyse its role in immunomodulation. Previous observations showed that addition of exogenous CDA is able to disperse mature biofilm and inhibit biofilm formation of different gram negative and gram positive bacteria such as PA, E. coli and S. aureus. The present study showed that exogenous addition of CDA is able to modify some aspects of the inflammatory response by modulating production of the pro-inflammatory cytokine TNF-α by human monocytes and macrophages. Thus the present study has identified the potential impact of CDA as an immune modulator which will offer many opportunities for development of drug with potential anti-inflammatory action.